2013
DOI: 10.1109/tcsi.2013.2264697
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Communication Network Performance From a Complex Network Perspective

Abstract: In this paper we study the performance of communication networks from a network science perspective. Our analysis and simulation results reveal the effects of network structure, resource allocation and routing algorithm on the communication performance. Performance parameters, including packet drop rate, time delay, and critical generation rate, are considered. For efficient data transmission, the traffic load should be as uniformly distributed as possible in the network and the average distance of it should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…A larger λ c implies that the network can transmit more traffic without congestion and λ c can be a measure of network traffic capacity. In our previous work [4], we have given a theoretical estimation of the critical generation rate λ c as follows:…”
Section: B Critical Generation Ratementioning
confidence: 99%
“…A larger λ c implies that the network can transmit more traffic without congestion and λ c can be a measure of network traffic capacity. In our previous work [4], we have given a theoretical estimation of the critical generation rate λ c as follows:…”
Section: B Critical Generation Ratementioning
confidence: 99%
“…Degree distribution is defined by a probability ( ), which is the proportion of the sensors with the same amount of connections. A graph of Erdös-Rényi random WSN has a vertex degree following the Poisson distribution as [33] …”
Section: Network Assumptions and Statistic Based Feature Modelmentioning
confidence: 99%
“…A similar concept named node usage probability can be used here to represent the ratio between the algorithmic betweenness of a node and the total algorithmic betweenness in each network [5]. Therefore,…”
Section: Modelmentioning
confidence: 99%
“…Traffic on such networked systems is a significant issue. A wealth of studies on traffic congestion from the perspective of an isolated complex network framework have been conducted over the past decade [2][3][4][5]. It has been widely revealed that traffic congestion is closely related to the network structure [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%